2007
DOI: 10.1080/07366290701416000
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Actinides with Different 6,6′‐Bis(5,6‐Dialkyl‐[1,2,4]‐Triazin‐3‐yl)‐[2,2′]‐Bipyridines (BTBPs)

Abstract: The extraction of Am(III), Th(IV), Np(V), and U(VI) from nitric acid by 6,6 0 -bis(5,6-dialkyl-[1,2,4]-triazin-3-yl)-[2,2 0 ]-bipyridines (C2-, C4-, C5-, and CyMe 4 -BTBP) was studied. Since only americium and neptunium extraction was dependent on the BTBP concentration, computational chemistry was used to explain this behavior. It has been shown that the coordination of the metal played an important role in forming an extractable complex into the organic phase, thus making it possible to extract pentavalent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 11 publications
(21 reference statements)
2
42
0
Order By: Relevance
“…Of these, hydrophobic bis(triazinyl)pyridines (BTP) [6] and bis(triazinyl)bipyridines (BTBP) [7][8][9] are the most promising candidates. However, none of them fulfil all criteria for application in an industrial process, hence requiring optimisation.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, hydrophobic bis(triazinyl)pyridines (BTP) [6] and bis(triazinyl)bipyridines (BTBP) [7][8][9] are the most promising candidates. However, none of them fulfil all criteria for application in an industrial process, hence requiring optimisation.…”
Section: Introductionmentioning
confidence: 99%
“…This enables the utilization of the specific properties of both extracting agents. The chosen ligands are 6,6ʹ-bis(5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-benzo [1,2,4] triazin-3-yl) [2,2ʹ]bipyridine (CyMe 4 -BTBP), [18,19] designed to extract tri-butyl and pentavalent actinides without extracting trivalent lanthanides, [20] and tri-butyl phosphate (TBP) (Figure 1), which is mainly for extracting tetra-and hexavalent actinides. [21] Combining these two extracting agents enables the necessity of redox control to be avoided, and it is possible to strip the actinides selectively or to reuse them directly in a homogeneous recycling.…”
Section: Introductionmentioning
confidence: 99%
“…100 The extraction of Am(III), Th(IV), Np(V), and U(VI) by a range of BTBP ligands has been investigated to determine the effect of the oxidation state of the actinide ions on their extraction. 102 It was found that the extraction increased in the order Am(III) < Th(IV) < Np(V) < U(VI) at low BTBP concentrations, but increased in the order Th(IV) < U(VI) < Np(V) < Am(III) at high BTBP concentrations. This study suggests that the tri-and pentavalent actinides can be separated from the tetra-and hexavalent actinides using the BTBPs.…”
Section: Scheme 8 Synthesis Of 66¢-bis(124-triazin-3-yl)-22¢-bipymentioning
confidence: 95%